2018
DOI: 10.1177/0003489418760055
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Snap & Sniff Threshold Test

Abstract: Based on validity and test-retest reliability, we concluded that the S&S is a proper test for olfactory thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A similar phenomenon was found in a previous study. 20 The results of the two different devices for the PEA odour detection threshold test, the Smell Threshold Test and the Snap & Sniff Threshold Test were correlated, and a significant correlation existed for hyposmic and anosmic patients, though not the normosmic subjects. 20 This might be partly explained by the definition of the normosmic subjects in the current study, which were healthy volunteers that self-reported an absence of olfactory deficits without a history of sinonasal symptoms within 1 week before the test.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar phenomenon was found in a previous study. 20 The results of the two different devices for the PEA odour detection threshold test, the Smell Threshold Test and the Snap & Sniff Threshold Test were correlated, and a significant correlation existed for hyposmic and anosmic patients, though not the normosmic subjects. 20 This might be partly explained by the definition of the normosmic subjects in the current study, which were healthy volunteers that self-reported an absence of olfactory deficits without a history of sinonasal symptoms within 1 week before the test.…”
Section: Discussionmentioning
confidence: 93%
“… 20 The results of the two different devices for the PEA odour detection threshold test, the Smell Threshold Test and the Snap & Sniff Threshold Test were correlated, and a significant correlation existed for hyposmic and anosmic patients, though not the normosmic subjects. 20 This might be partly explained by the definition of the normosmic subjects in the current study, which were healthy volunteers that self-reported an absence of olfactory deficits without a history of sinonasal symptoms within 1 week before the test. Their olfactory function was not examined to confirm whether they were normosmic using a PEA test because it needs the examinee to take off their facemask in front of the examiner, which is not recommended during the current COVID-19 pandemic status.…”
Section: Discussionmentioning
confidence: 93%
“…Snap is a series of olfaction tests similar to Sniffin’ Sticks, but delivers odors via a slide mechanism. Snap measures threshold (1.5–9.5), discrimination (0–22), and identification (0–16) domains 3,6 . Snap TDI score ranges from 1.5 to 47.5.…”
Section: Methodsmentioning
confidence: 99%
“…Snap measures threshold (1.5-9.5), discrimination (0-22), and identification (0-16) domains. 3,6 Snap TDI score ranges from 1.5 to 47.5.…”
Section: Psychophysical Testingmentioning
confidence: 99%
“…These tests measure domains of olfaction (eg, threshold, discrimination, identification) and the majority of employed odorants are pleasurable or neutral odors. [11][12][13][14] Psychophysical tests, therefore, provide information on the ability to detect and differentiate odors, but do not necessarily comment on other forms of parosmia, including those related to altered perception in hedonics (eg, phantosmia). One of the earliest olfactory tests reported in scientific literature used a method of chemosensory testing involving 4 odors and 4 domains of olfaction (herein referred to as "Henkin Test").…”
Section: Introductionmentioning
confidence: 99%